Central-Local Government dalam Manajemen Bencana Pandemi COVID-19 di Indonesia - Rumzi Samin (Jayapangus Press, 2021)
The relationship between the local government and the central government in handling COVID 19 in Indonesia is considered very bad because the existing disaster management is considered slow in breaking the chain of the spread of COVID 19. This study focuses on coordination between the central government and local governments where there are many mismatched statements in determining policies in handling COVID 19 which is confusing in the application of handling this COVID 19 disaster. The research method using a systematic literature review is one approach to the literature review method by describing the procedure for selecting publication criteria and/or literature that is reviewed with the aim of getting a broad picture related to a particular topic or issue. The results of the study indicate the need for principles of interaction between local and central government authorities in the task of handling the COVID-19 disaster that has not used a good disaster management strategy, this is because it does not implement the relationship responsibility principles of central-local government interaction so it is necessary to strengthen communication. In addition, during the COVID-19 pandemic, there is a complicated bureaucratic system in central-local government interactions